2014
DOI: 10.1007/s10533-014-0038-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hydro-sedimentary processes on the dynamics of soluble reactive phosphorus in the Seine River

Abstract: International audienceThis paper focuses on soluble reactive phosphorus (SRP) dynamics along a 225 km stretch of the Seine River, including the Paris urban area, for the 2007–2011 period. The impact of hydro-sedimen-tary processes on SRP concentrations and fluxes is estimated under various hydrological conditions. Sorp-tion interaction parameters between SRP and sus-pended matter are experimentally determined on river water samples and are included in a hydro-ecological model. Simulated concentrations are comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 90 publications
3
29
1
Order By: Relevance
“…The largest variations in the adsorption–desorption process occur in the winter (+3% and +22% for wet and dry years, respectively), while summer values range between +7% and +12%. This is in accordance with the results of Vilmin et al (), who found that in the upstream Seine River, the release of reactive phosphorus by the riverbed sediments occurred mainly during high‐flow periods, i.e., in the winter time. The contrasting release of P between summer/winter periods and dry/wet years may thus be the result of a compromise between sufficient flow to dilute P concentrations in the water column and to induce mixing and sediment resuspension, and enough residence time to allow for the exchange.…”
Section: Discussionsupporting
confidence: 93%
“…The largest variations in the adsorption–desorption process occur in the winter (+3% and +22% for wet and dry years, respectively), while summer values range between +7% and +12%. This is in accordance with the results of Vilmin et al (), who found that in the upstream Seine River, the release of reactive phosphorus by the riverbed sediments occurred mainly during high‐flow periods, i.e., in the winter time. The contrasting release of P between summer/winter periods and dry/wet years may thus be the result of a compromise between sufficient flow to dilute P concentrations in the water column and to induce mixing and sediment resuspension, and enough residence time to allow for the exchange.…”
Section: Discussionsupporting
confidence: 93%
“…It is composed of three modules, which compute hydrodynamic, transport and biogeochemical processes, in the water column and the benthic sediment. The ProSe model has been applied successfully to several case studies in the Seine River basin (Even et al, , 2007bFlipo et al, 2004Flipo et al, , 2007Polus et al, 2010Polus et al, , 2011Vilmin et al, 2015a) and in the Seine Estuary (Even et al, 2007c). The role of benthic sediments has been recently improved by recalibration of the sediment erosion processes in the PROSE model (Vilmin et al, 2015b).…”
Section: Hydro-ecological Model (Prose)mentioning
confidence: 99%
“…The longitudinal profiles of the simulated concentration quantiles (10%, 50% and 90%) were compared to weekly observations at ten stations managed by the SIAAP and eight stations of the national river monthly monitoring network (R eseau de Contrôle et de Surveillance, referred to as RCS) along the studied stretch. The longitudinal profiles of the biomasses of ammonia and nitrite oxidizers from the Seine River and the SAV effluent were compared at low and high water discharge conditions, following the approach developed to analyse inriver sediment (Vilmin et al, 2015b) and phosphorus (Vilmin et al, 2015a) dynamics. The distinction between low and high discharge conditions was based on the daily discharge measured at the Paris gauging station (Fig.…”
Section: Hydro-ecological Model (Prose)mentioning
confidence: 99%
“…3), the majority of them were used to describe bacteria and phytoplankton dynamics depending on light intensity, water temperature, and nutrient availability. Most coefficients are currently accepted as universal constants, but several studies pointed out that hydro-sedimentary and P sorption/desorption processes needed experimental or numerical calibration (Vilmin et al, 2015), especially because the processes involved highly impacted performances on phytoplankton and water quality predictions (Aissa-Grouz, 2015). Phosphorus dynamic in the water compartment was based on the Langmuir equilibrium concept (Limousin et al, 2007), a description largely found in the literature for water quality models (e.g.…”
Section: Calibration Stepmentioning
confidence: 99%
“…Phosphorus dynamic in the water compartment was based on the Langmuir equilibrium concept (Limousin et al, 2007), a description largely found in the literature for water quality models (e.g. Chao et al, 2010;Rossi et al, 2012;Vilmin et al, 2015). Very different values for P sorption/desorption coefficients according to Langmuir equilibrium equations were found experimentally or numerically in the literature, with up to 5 orders of magnitude differences from one study to another (Vilmin et al, 2015).…”
Section: Calibration Stepmentioning
confidence: 99%